Polyethylene end-use properties and their physical meaning - Kissin, Y. V. (Hanser Publishers, 2013)
This book provides a necessary bridge between the values of engineering end-use parameters of polyethylene resins and their scientific molecular and structural characteristics. The main goal is to translate such common parameters, such as the melt index of a resin or the dart impact strength of a film sample, into the universal language of the polymer science. After this translation is completed, many facets of the resin properties became transparent and easily explainable.
Keywords: Polyethylene -- Mechanical properties.; Molecular weights.; Gums and resins, Synthetic.; elektronické knihy; electronic books